Public Service Motivation Leveling pada Aparatur Sipil Negara di Lingkungan Kantor Imigrasi Kelas I Non TPI Tangerang - Gunawan Ari Nursanto; Arief Febrianto; Rita Kusuma Astuti; Vira Widhaningsih; Hanifa Maulidia; Besse Hartati (J-MAS (Jurnal Manajemen dan Sains), 2023)
The performance of the State Civil Apparatus which is further abbreviated as (ASN) is crucial and interesting to discuss, it is related to the image of the organization and competence in carrying out tasks within the organization. An ASN with good performance will certainly display a good image for the organization as well. The aspect that needs to be given special attention by the government in the motivational aspect is internal motivation. One of the internal motivations that can improve employee performance is public service motivation. This study used quantitative methods and took place at the Class I Immigration Office in Tangerang with 109 ASN (State Civil Apparatus) respondents at the office. This study aims to find significant differences in the level of public service motivation among civil servants based on demographics. This study found that there were no significant differences in the level of public service motivation based on position and educational background. However, there were significant differences in the level of public service motivation based on age and gender.